2019
DOI: 10.1371/journal.pone.0215791
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of presepsin considering renal function

Abstract: Presepsin, a glycoprotein produced during bacterial phagocytosis, is used as a sepsis marker for bacterial infections. However, presepsin levels are affected by renal function, and the evaluation criteria according to kidney function or in chronic kidney diseases remain controversial. Furthermore, presepsin may be increased by sample stirring, but no studies have evaluated this effect.In this study, we excluded the effect of stirring by standardizing the blood collection conditions, analyzed the influence of k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…Although this study was conducted in patients without any evidence of bacterial infection or sepsis, similar results have been demonstrated in septic patients with and without AKI [66], leading to the conclusion that PCT has much better diagnostic accuracy in patients with AKI than presepsin. An increase in presepsin was also noted in AKI patients without sepsis, in line with the finding of Miyoshi and co-workers [89]. It is important to ensure that the correct analytical target is measured; one study described the use of presepsin, but closer inspection revealed that they had actually measured soluble CD14 and not presepsin (soluble CD14 subtype) [90].…”
Section: Adults Icusupporting
confidence: 76%
See 2 more Smart Citations
“…Although this study was conducted in patients without any evidence of bacterial infection or sepsis, similar results have been demonstrated in septic patients with and without AKI [66], leading to the conclusion that PCT has much better diagnostic accuracy in patients with AKI than presepsin. An increase in presepsin was also noted in AKI patients without sepsis, in line with the finding of Miyoshi and co-workers [89]. It is important to ensure that the correct analytical target is measured; one study described the use of presepsin, but closer inspection revealed that they had actually measured soluble CD14 and not presepsin (soluble CD14 subtype) [90].…”
Section: Adults Icusupporting
confidence: 76%
“…It is interesting to note that the 19 studies they reviewed were all observational; no randomised controlled trials were found, which resulted in the evidence being considered of low quality. Miyoshi and co-workers demonstrated that the concentration of presepsin is influenced by renal function, and that there is a correlation between declining renal function and increasing presepsin concentration [89]. Although this study was conducted in patients without any evidence of bacterial infection or sepsis, similar results have been demonstrated in septic patients with and without AKI [66], leading to the conclusion that PCT has much better diagnostic accuracy in patients with AKI than presepsin.…”
Section: Adults Icusupporting
confidence: 63%
See 1 more Smart Citation
“…A range of presepsin levels in the absence of acute pathology was established for individuals with normal renal function compared with patients with chronic renal failure. Individuals with grade 3, 4 and 5 renal failure had baseline presepsin values significantly above the other group, with values of 208.1 ± 70.2 pg/mL, 320.2 ± 170.1 pg/mL, 712.8 ± 336.3 pg/mL, respectively [54]. Three studies on patients presenting with acute kidney injury and sepsis indicated that in the validity of presepsin measurement in this population was reduced [55,56] and procalcitonin was superior as a diagnostic and prognostic marker of sepsis in this group [57].…”
Section: Presepsin and Renal Failurementioning
confidence: 89%
“…Presepsin is one of the new inflammatory markers and been found to inversely correlated with GFR. 17,19,20 Furthermore, in HD patients, presepsin levels are significantly higher than in grade 5 CKD patients. 17 Similarly, in the present study, the overall presepsin level in HD patients was 14 times higher than renal-healthy controls.…”
Section: Discussionmentioning
confidence: 99%